2014
DOI: 10.1063/1.4871396
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation requirements for the Richtmyer-Meshkov instability

Abstract: The shock induced mixing of two gases separated by a perturbed interface is investigated through Large Eddy Simulation (LES) and Direct Numerical Simulation (DNS). In a simulation, physical dissipation of the velocity field and species mass fraction often compete with numerical dissipation arising from the errors of the numerical method. In a DNS the computational mesh resolves all physical gradients of the flow and the relative effect of numerical dissipation is small. In LES, unresolved scales are present an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The results suggest that although the time window of simulations has been extended thanks to the hybrid method, the flow has not yet become fully self-similar. Olson and Greenough (2014) suggested that the required number of grid points needed for a DNS of RMI is about 4 × 10 12 , which exceeds the current capabilities of super-computing resources. For an RM calculation with fixed small scales computed with an explicit hydrodynamics scheme, the computational cost to get to width W will be ∝ W 3 W 1/θ , where the first term is the number of cells required to resolve the mixing layer and the second term is the number of timesteps required.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that although the time window of simulations has been extended thanks to the hybrid method, the flow has not yet become fully self-similar. Olson and Greenough (2014) suggested that the required number of grid points needed for a DNS of RMI is about 4 × 10 12 , which exceeds the current capabilities of super-computing resources. For an RM calculation with fixed small scales computed with an explicit hydrodynamics scheme, the computational cost to get to width W will be ∝ W 3 W 1/θ , where the first term is the number of cells required to resolve the mixing layer and the second term is the number of timesteps required.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of initial conditions build on previous studies [11,13,18,20,21] and have the following features:…”
Section: A Standard Problemmentioning
confidence: 99%
“…Thus a direct comparison of integral properties between all prior studies is not possible. Furthermore, of all prior studies, only four include computations using more than one algorithm for the same initial condition [11,13,14,18], each of them using two independent algorithms. It is not possible to obtain a robust estimate of numerical uncertainty with such a limited sample.…”
Section: Introductionmentioning
confidence: 99%
“…Previous published direct numerical simulations of RMI include a study by Olson and Greenough [18], as well as the studies of Tritschler et al [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In [18], single-shock RMI in air and sulphur hexafluoride (SF 6 ) initiated by a Mach 1.18 shock was analysed using two different numerical methods.…”
Section: Introductionmentioning
confidence: 99%